2001
DOI: 10.1007/pl00001933
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Clinical Investigation of the Impact of Early Treatment of Children with Down's Syndrome According to Castillo-Morales

Abstract: Early treatment using a stimulation plate thus appears to mitigate or even normalize the initially more severe dysfunctions recorded in the study group as compared to the controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
12

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 14 publications
1
15
0
12
Order By: Relevance
“…It was observed that the reaction to inserting the plate was the strongest in the early months of treatment; this was reported by the parents of children with Down syndrome in the current study, but has also been mentioned by other authors [17,23]. Good plate adaptation in the youngest children was observed by Schuster and Giese [16], who used photographic documentation and questionnaires to assess the effects of stimulating plate treatment as part of Castillo-Morales therapy implemented in the early stages of development of children with Down syndrome. In older children becoming discouraged with the palatal plate may be connected with the eruption of teeth, which was also observed by Bäckman et al [24].…”
Section: Internetsupporting
confidence: 88%
See 1 more Smart Citation
“…It was observed that the reaction to inserting the plate was the strongest in the early months of treatment; this was reported by the parents of children with Down syndrome in the current study, but has also been mentioned by other authors [17,23]. Good plate adaptation in the youngest children was observed by Schuster and Giese [16], who used photographic documentation and questionnaires to assess the effects of stimulating plate treatment as part of Castillo-Morales therapy implemented in the early stages of development of children with Down syndrome. In older children becoming discouraged with the palatal plate may be connected with the eruption of teeth, which was also observed by Bäckman et al [24].…”
Section: Internetsupporting
confidence: 88%
“…It comprises multidisciplinary medical care provided by pediatricians, geneticists, neurologists, psychologists, speech therapists and, more and more frequently, orthodontists as well. Regardless of the difficulty involved in assessing changes in mimetic muscle tension, tongue position and lip closure during and after palatal plate therapy, visual assessment remains one of the most important methods of assessing the progress of orofacial rehabilitation through the use of a palatal plate [12,16]. Carlstedt et al [17,18] used video recordings to assess the progress of rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…cial function." The present follow-up study takes up Carlstedt's concerns in that the follow-up period of more than 12 years offers a greater predictive potential with respect to long-term stability than other studies [5,8,9,16,21,32] with a shorter follow-up period.…”
Section: Adjuvante Therapien (Elternfragebogen)mentioning
confidence: 86%
“…Supported by motivated physiotherapists and driven by intensified suffering-induced pressure, parents of children with a pronounced dysfunction tend to display more intensive compliance [32].…”
Section: Adjuvante Therapien (Elternfragebogen)mentioning
confidence: 99%
See 1 more Smart Citation